ANALISIS PENGARUH JAM BELAJAR TERHADAP INDEKS PRESTASI KUMULATIF (IPK) MAHASISWA TEKNIK SIPIL UNIVERSITAS INTERNASIONAL BATAM - Steven Shui; Mahfuz Hudori; Melvin Wishly; Wijaya Wijaya (Nusantara Hasana Berdikari, 2022)
The Grade Point Average (GPA) is the score that student get cumulatively from the first semester to the final semester. In this study, a survey was conducted on Civil Engineering students at Universitas International Batam. This study uses pearson correlation analysis and simple regression as statistical methods in processing and analyzing research data. The results of correlation and simple regression analysis show that there is a relationship between study hours and the Grade Point Average (GPA) and the length of student study hours significantly affects the Grade Point Average (GPA) of Civil Engineering students at Universitas International Batam.